Prognostic Factor of H-Zone Area in Basal Cell Carcinoma - Mawardi, Prasetyadi; Prihadi, Irfany Arafiasetyanto; Irawanto, Muhammad Eko (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The study data were taken from secondary data obtained from medical records of BCC patients in Dr. Moewardi Hospital. The data were categorized based on gender, age, occupation, predilection/ location of tumor based on Baxter criteria, which divided the area into H-zone dan non-H-zone. H-zone was described to cover temporal, auricular, orbital, nasal, upper mandibular. Whereas the tumor size was divided into two, less than 2 cm and more than 2 cm. H-zone is a predilection with a high risk toward tumor biological characteristics, such as recurrence risk, aggressivity risk, and tumor infiltrative. The study obtained an ethics clearance from Health Research Ethics Committee of Dr. Moewardi Hospital with number 762/VIII/HREC/2021. The analysis was conducted to test whether there was a correlation or effect between two variables or more. In the study, the researcher also conducted statistics test to measure the correlation intensity of two variables or more by using Chi-square (X2), statistics test was conducted by using SPSS 22 for Windows. 99 patients were obtained from the medical records however only 70 patients who met the study requirements, who were subsequently categorized based on gender, age, occupation, BCC location and size, disease duration. 29 patients were excluded due to incomplete medical records (BCC location, BCC size, and treatment history were not found) non-primary BCC, data duplication, patients with more than one medical records, the result of histopathological test did not indicate seborrheic keratosis and Squamosa Cell Carcinoma. Based on the study there were more female patients compared to male patients. it discovered 45 female patients and 25 male patients (64,3% compared to 35,7%), with the age range was from 22-90 years, the BCC tumor was endured for more than 2 years, based on the education most of the patients had primary education background (elementary school and junior high school), the majority occupation of the patients was farmer (30%), followed by housewife (28,57%).